ACCULTURATION OF ISLAM AND LOCAL CULTURE IN THE TRADITION OF BUFFALO SACRIFICE IN BONDER VILLAGE, CENTRAL LOMBOK - Daniati, Nia; mas'ud, Hadlun; saliki, Saliki; Zulhaiki, Zulhaiki (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
The research explores what Islamic values can be learned in the selamatan tradition, and how the acculturation of Islam and local culture in Bonder Village, West Praya Sub-district, Central Lombok Regency. This research uses analytical descriptive qualitative research. Data collection techniques include interviews, observation, and documentation, data analysis includes reduction, presentation, conclusion drawing, and verification. The data validity test was carried out by triangulating the source and source techniques. The results of this study indicate that the purpose of this buffalo salvation tradition is so that the buffalo that is saved is not afflicted by supernatural diseases, and so that the buffalo is given safety to be able to breed safely. Implementation. This buffalo rescue ceremony has Islamic values that can be learned such as, the value of Tauhid, Ibadah, Akhlak, and Silaturrahmi. Islamic acculturation in this buffalo rescue tradition can be said to control each other, in other words, give and take, this can be seen when celebrating this tradition, Islamic values are always inserted in the local cultural system. This shows that Islam and local culture are able to guide people from what is not expected.